PENERAPAN APLIKASI SAIBA UNTUK PENYUSUNAN LAPORAN KEUANGAN - Arieffin Dian Permana (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2016)
ABSTRACT Information technology (IT) have a great impact to all over environmental society, especially for bussines and accounting. Nowdays, information technology is already used in government sectors. Society are prosecute government sektors works efficiently and effectively to give a excellent public services, because the objectives of government sectors is to produce better pulic services. One of government sectors responsibility for society is to produce financial statement. Financial statement represent the performance of government sectors. Financial statement is arranged according to goverment standards and laws. Implementation of good governance in government sectors, makes a great revolution on government accounting basis. Prior the implementation of good governance, accounting basis for government sectors is a cash basis. Now the standards requires accrual basis to be used in addition to report financial statement. This differences makes a adjustments are needed on the government financial reporting process. Then, government launch SAIBA (Sistem Akuntansi Instansi Berbasis Accrual) to accommodate this conditions.  The writer main focussed is to describe the characteristic, advantages, and disadvantages of application but not how to this applications works. Keywords : Information Technology, Good Governance, SAIBA, Financial Statement, Cash Basis, Accrual Basis.